HIERARCHICAL CLUSTERING IN ECORACES OF TROPICAL TASAR SILKWORM, ANTHERAEA MYLITTA DRURY BASED ON QUANTITATIVE TRAITS - A. K. SRIVASTAVA,; P. K. KAR,; M. K. SINHA,; S. RAI,; B. C. PRASAD, (The Bioscan, 2011)
Tasar silkworm, Antheraea mylitta Drury is a commercially utilized sericigenous insect distributed over a wide forest range of Indian subcontinent. Varied topographical features, climatology, vegetation and edaphic factors in different regions have resulted in the diversity in the phenotypic, physio-genetic, behavioural and commercial characters of this silkworm. It is variability, which had led the taxonomists to the establishment of several species and sub-species of this insect. A detailed study was carried out to understand the wide variations and for the purpose, exploratory surveys were conducted in 10 states of India and 28 ecoraces were collected. Observations on regional ecology, reproductive behaviour and commercial attributes were made. Analysis indicated tremendous inter as well as intra-population variability between and within the ecoraces of A. mylitta. Based on multivariate analysis, 28 ecoraces were grouped in seven clusters. Observations reveal that there is no clear cut relationship with the genetic diversity and geographical origin of the ecoraces of A. mylitta. The populations of this insect species are declining alarmingly in their natural habitats due to forest destruction and rampant collection of wild cocoons for the cause of silk industry. Hence, adoption of conservation measures is the need of the hour.